1999
DOI: 10.1177/000331979905000502
|View full text |Cite
|
Sign up to set email alerts
|

The Exercise Pressor Reflex and Changes in Radial Arterial Pressure and Heart Rate During Walking in Patients with Arteriosclerosis Obliterans

Abstract: Little is known about the time course and extent of the changes in radial arterial pressure and heart rate taking place in patients with arteriosclerosis obliterans during walking, as well their subtending mechanisms. For this reason the authors measured these variables in 23 patients with arteriosclerosis obliterans and in nine normal subjects (control group), during treadmill walking and several tests. In the patients a rapid and marked increase in radial arterial pressure was recorded during walking, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 13 publications
(2 reference statements)
2
37
0
Order By: Relevance
“…These results suggest that cardiovascular responses during constant load exercise are exaggerated in patients with PAD. Previous studies have shown that cardiovascular responses during constant load exercise are greater in PAD patients than in healthy subjects (3, 4). In addition, changes in HR and BP described in subjects with left ventricular dysfunction (2) were lower than the ones observed in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results suggest that cardiovascular responses during constant load exercise are exaggerated in patients with PAD. Previous studies have shown that cardiovascular responses during constant load exercise are greater in PAD patients than in healthy subjects (3, 4). In addition, changes in HR and BP described in subjects with left ventricular dysfunction (2) were lower than the ones observed in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Cardiovascular responses during walking are altered in patients with PAD(3, 5). Previous studies have reported that blood pressure (BP) and heart rate (HR) both increase during constant load exercise in patients with PAD, but not in age matched controls(5).…”
Section: Introductionmentioning
confidence: 99%
“…PAD affects 8 to 12 million people in the United States, and those people are at a high risk for myocardial infarction and stroke (Criqui et al, 1992, Hirsch et al, 2001). PAD reduces blood flow to working skeletal muscle and results in an augmented blood pressure response to dynamic exercise that is thought to be caused in part by an exaggerated exercise pressor reflex (Baccelli et al, 1999, Bakke et al, 2007), part of which is thought to be evoked by mechanoreceptors (Muller et al, 2012). Oxidative stress has also been shown to play a role in the exaggerated pressor reflex in PAD.…”
Section: Exercise Pressor Reflex In Pad Patientsmentioning
confidence: 99%
“…The submaximal exercise task was not only more challenging metabolically for those with diabetes, but it also elicited a more exaggerated cardiovascular response, measured by a higher systolic blood pressure during ambulation than compared to the non-diabetic controls. It is possible that the higher exercise systolic blood pressure in participants with type 2 diabetes was related to greater endothelial dysfunction [22] or greater activation of the pressor reflex [23]. …”
Section: Discussionmentioning
confidence: 99%